Zero Waste sebagai Metode Sustainable Green Economy (Ekonomi Hijau Berkelanjutan) - Haryo Kusumo, Raden Akhmad; Rokhmatulloh, Muhammad Raisa Haqqiquddin (Reinforce: Journal of Sharia Management, 2025)
This study examines the integration of the green economy, zero waste, and Islamic economics to establish a sustainable and inclusive economic system. The research is motivated by increasing environmental challenges due to resource exploitation and the urgent need for a more sustainability-oriented economic approach. The objective is to analyze how Islamic economic principles can support the implementation of a green economy and zero waste as solutions to environmental and social issues. This study employs a qualitative literature review method, analyzing scientific journals, academic books, and reports from international institutions such as UNEP (United Nations Environment Programme) and Bappenas to gain a comprehensive understanding. The findings indicate that integrating Islamic economic principles with the green economy and zero waste can enhance resource efficiency, minimize environmental impact, and foster a more equitable and sustainable financial system. This study concludes that adopting these concepts in economic and environmental policies is crucial to ensuring long-term societal and ecological well-being.